Genome-Wide Identification of the GPAT Family in Medicago sativa L. and Expression Profiling Under Abiotic Stress - Jianzhi Ma; Mingyang Du; Huiyan Xiong; Ruijun Duan (Plants)
Glycerol-3-phosphate acyltransferase (GPAT), as a rate-limiting enzyme engaged in lipid synthesis pathways, exerts an important role in plant growth and development as well as environmental adaptation throughout diverse growth stages. Alfalfa (Medicago sativa L.) is one of the most significant leguminous forages globally; however, its growth process is frequently exposed to environmental stress, giving rise to issues such as impeded growth and decreased yield. At present, the comprehension of the GPAT genes in alfalfa and their reactions to abiotic stresses is conspicuously deficient. This study identified 15 GPATs from the genome of “Zhongmu No. 1” alfalfa, which were phylogenetically categorized into three major groups (Groups I ~ III). Furthermore, Group III is further subdivided into three distinct subgroups. MsGPATs belonging to the same subfamily exhibited similar protein conserved motifs and gene structural characteristics, in which groups with simple conserved motifs had more complex gene structures. A multitude of regulatory cis-elements pertinent to hormones and responses to environmental stress were detected in their promoter regions. In addition, a spatial–temporal expression analysis showed that MsGPATs have significant tissue specificity. Furthermore, the transcriptomic analysis of ABA treatment and the qRT-PCR results under drought, salt, and cold stress demonstrated that the majority of MsGPATs respond to abiotic stress with pronounced timely characteristics. It was also ascertained that these GPAT genes might assume a crucial role in salt and drought stress. This research can further constitute a fundamental basis for the exploration of the alfalfa GPAT family, the screening of key GPATs, and the investigation of their functionalities.